S55c carbon steel for heat treatment process with different medium in attenuation measurement using ultrasonic testing - Ali K.; Paw J.K.S.; Aizat M.Sulaiman M.; Abdalla A.N.; Hen C.K.; Ding T.J. (Science Publishing Corporation Inc, 2023)
Ultrasonic testing or commonly known as UT is one of the non-destructive testing technique and widely used in oil and gas industrial inspection. This technique mostly used in defect or crack identification of the pipeline and also used for flaw detection/evaluation, dimensional measurements, and material characterization. This paper presents the effect of heat treatment for S55C carbon steel in attenuation measurement by using ultrasonic testing including annealing, tempering, and quenching process. Seawater and oil are used as a medium of quenching process. The fixed excitation frequency at 4 MHz is used and 0 degrees with double crystal is implemented in this measurement. The thicknesses of blocks used are as the sample from 30mm until 80mm. The result shows that the measurement of material attenuation will be decreased after annealing, tempering and quenching process from 40% until 99% compared to before the heat treatment process. The highest attenuation decreasing can be seen on the sample block with the 30mm thickness in the heat treatment process. 2018 Authors.